Social support for students in difficult situations - Klimas Ilona; Pelc Karolina; Kopytko Sylwia (Borys Grinchenko Kyiv Metropolitan University, 2018)
The article refers to ways of supporting students in difficult situations. This paper presents the definition of support and difficult situations, taking into account their types and the characteristics of these issues. Surveys were conducted at primary school in Rzeszów among students of grades VI and VII, which indicated the most frequent forms of help for students and the frequency of difficult situations experienced by young people. The survey was carried out by means of a questionnaire.